Assessing the predictive potential of ADAM8 for disease control in chronic rhinosinusitis with nasal polyps - Liu, Peiqiang; Liu, Meng; Sun, Yibin; Lei, Weiwei; Xu, Yu (Frontiers in Allergy, 2024)
BackgroundA disintegrin and metalloproteinase 8 (ADAM8) has been implicated in eosinophilic inflammation; however, its role in chronic rhinosinusitis with nasal polyps (CRSwNP) remains to be elucidated. This study aimed to investigate the predictive significance of ADAM8 levels in nasal secretions for the endotypes and disease control status of CRSwNP.MethodsA cohort comprising 120 CRSwNP patients and 45 healthy controls (HCs) was assembled, delineating 53 non-eosinophilic CRSwNP (neCRSwNP) and 67 eosinophilic CRSwNP (eCRSwNP) patients. Immunohistochemistry and enzyme-linked immunosorbent assay (ELISA) were utilized to measure ADAM8 levels in nasal mucosal tissues and secretions from all participants. The receiver operating characteristic (ROC) curves and Pearson correlation analysis were employed to assess the predictive capability of ADAM8 levels in predictiving CRSwNP endotypes and disease control status.ResultsADAM8 levels in nasal secretions were elevated in CRSwNP patients compared to HCs, with a more pronounced increase observed in eCRSwNP patients. Elevated ADAM8 concentrations in nasal secretions were positively correlated with peripheral blood eosinophil counts and percentages, tissue eosinophil counts, serum total IgE, Lund–Mackay scores, and Lund-Kennedy scores. Ultimately, 103 CRSwNP patients completed the follow-up protocol, with 72 classified as the controlled group and 31 as the uncontrolled group. Uncontrolled CRSwNP patients exhibited significantly higher ADAM8 levels in nasal secretions compared to the controlled group. The ROC curves indicated that ADAM8 in nasal secretions exhibits robust discriminatory capacity for eCRSwNP and postoperative disease control status.ConclusionADAM8 in nasal secretions emerges as a potential novel biomarker for the prognostication of CRSwNP endotypes and the postoperative disease control status.